SEKTOR PERTANIAN DAN PERANNYA DALAM PENYERAPAN TENAGA KERJA DI KABUPATEN BURU - Tri Wahyuningsih (MediaTrend, 2015)
The aim of this study is the first, investigate and analyze how much employment in the agricultural sector in Buru; second, identify and analyze the level of labor productivity in the agricultural sector in Buru; Third, to know and analyze how much force multipliers agricultural sector in Buru; Fourth, make predictions employment in the agricultural sector from 2006 to 2020. The method used for analysis is the employment elasticity, labor productivity, employment multipliers, and pure forecasts. The results obtained are: First, the employment opportunities in the agricultural sector experienced in KabupatenBuru fluctuate every year, of which the highest employment have occurred in 2002 in the amount of 121.91 percent and the lowest employment occurred in 2010 amounted to -13, 41 percent, while in 2013 the agricultural sector employment reached 3.58 percent; Second, the level of labor productivity in the agricultural sector experienced the lowest Buru regency in 2012 amounted to 4.33 percent, whereas in 2013 the productivity of the agricultural sector by 3.87 percent; Third, another sector employment opportunities created by the agricultural sector in Buru is fluctuating. Increase employment opportunities in other sectors of the largest occurred in 2003 abaout5 people. While the lowest employment multiplier in the period 2001 to 2013 there were in 2012, namely 1 to 2; Fourth, using an assumption of employment elasticity of 3.58 and 17.56 for employment growth as experienced in 2013, the employment opportunities in the agricultural sector Buru expected to increase in 2016 to 2020.